PENCEGAHAN TINDAK PIDANA KORUPSI OLEH SATUAN TUGAS TIM SAPU BERSIH PUNGUTAN LIAR DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI PERUBAHAN ATAS UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG TINDAK PIDANA KORUPS - Dias Agung Robihasad (Iustitia Omnibus (Jurnal Ilmu Hukum), 2020)
The crime of corruption as an extraordinary crime (extra ordinary crime) in the handling of require determination and a strong effort from government law enforcement is no exception. The perpetrator of the criminal offence of corruption already comes from many quarters both civil servants and private organisers even State, based on the issues examined by the author, then the normative legal research methods. Normative legal research methods or methods of legal research library is the method or manner used in legal research conducted by way of researching the existing library materials, it can be concluded that led to charges Wild there are four factors, economic factors, i.e. factors the existence of opportunity, lack of awareness and a plurality of perpetrators of the wild, and the levy is not good but intentional.